Placemaking Through Sensory Engagement: Assessing Cultural Essence of Assi Ghat, Varanasi for Virtual Environments - Tejaswini Rai; Suruchi Modi; Neena Zutshi (IAFOR Journal of Cultural Studies)
Assi Ghat, one of the most prominent places in India, and incorporating the steps leading down to the sacred river Ganges in Varanasi, is a microcosm of the city’s spiritual, cultural, and social life. This paper explores the sensory experiences at the cultural landscape site Assi Ghat, focusing on how these experiences shape the identity of the space and contribute to the overall experience of visitors and pilgrims. The built fabric of the ghat (from Sanskrit Ghatta, steps leading to a river), along the sacred river Ganges, is not merely a geographical location but a multisensory environment where the sights, sounds, smells, and textures all play a crucial role in creating a deep, immersive experience and spiritual connection with the sacred environment. Various activities at the ghat, such as the morning prayers (Aarti), yoga sessions, and cultural performances become integral to this sensory landscape, influencing how both locals and visitors perceive and interact with the space. The study discusses the importance of sensory experiences in public spaces, particularly in the context of placemaking at cultural landscapes, where these elements contribute to the creation of meaningful and engaging environments. Additionally, the paper explores the concept of digital placemaking, suggesting that the sensory richness of Assi Ghat could be preserved and replicated in a digital environment. The study emphasizes the need to integrate sensory experiences into both physical and digital placemaking efforts to maintain the cultural and spiritual essence of Assi Ghat, ensuring that its unique atmosphere is preserved for future generations.